DAMPAK PENGGUNAAN SISTEM INFORMASI AKADEMIK UNTUK MENINGKATKAN KUALITAS PELAYANAN AKADEMIK MAHASISWA UNIVERSITAS ANDALAS PADANG - Yindrizal, Yindrizal (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2021)
The development of Information Technology is handled positively by Andalas University, namely by establishing an Academic Information System (SIA) to improve data quality, information quality and service quality. The Academic Information System is an added value for Andalas University in providing academic administration services to students. Using Academic Information Systems can reduce interactions between students and academic administrative staff so that services are more effective and efficient. This is in line with student expectations, but not all of them are in line with expectations because students are required to manually re-register in each study program. In addition, there is still inaccurate information presented by the Academic Information System and the socialization has not been maximized. This problem is the homework of the Computer Information Technology Development Institute (LPTIK) as the manager of the Andalas University academic information system